Design and implementation of a VBR continuous media file server. - Makaroff, D. (IEEE Transactions on software engineering)
We describe the design and implementation of a file server for variable bit rate continuous media. We address the problem of building a server where each stream may have a different bit rate and, more importantly, where the bit rate within a single stream may vary considerably. Such a server has been implemented within a high-speed network environment. The server is designed to be used in a heterogeneous environment and is linearly scalable. A significant aspect of the design of the system is the detailed consideration of the variable bit-rate profile of each data stream in performing admission control for the disk and for the network. This paper describes the system model, the user interface design, implementation details, and performance results based on initial experience with the server